Prone Position Ventilation in Neurologically Ill Patients: A Systematic Review and Proposed Protocol. Issue 3 (22nd January 2021) - Wright, James M.; Gerges, Christina; Shammassian, Berje; Labak, Collin M.; Herring, Eric Z.; Miller, Benjamin; Alkhachroum, Ayham; Kottapally, Mohan; Huang Wright, Christina; Rodgers, Richard B.; Sedney, Cara; Ngwenya, Laura B.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Prone positioning has been shown to be a beneficial adjunctive supportive measure for patients who develop acute respiratory distress syndrome. Studies have excluded patients with reduced intracranial compliance, whereby patients with concomitant neurologic diagnoses and acute respiratory distress syndrome have no defined treatment algorithm or recommendations for management. In this study, we aim to determine the safety and feasibility of prone positioning in the neurologically ill patients. DESIGN AND SETTING: A systematic review of the literature, performed in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analyses 2009 guidelines, yielded 10 articles for analysis. Using consensus from these articles, in combination with review of multi-institutional proning protocols for patients with nonneurologic conditions, a proning protocol for patients with intracranial pathology and concomitant acute respiratory distress syndrome was developed. MEASUREMENTS AND MAIN RESULTS: Among 10 studies included in the final analysis, we found that prone positioning is safe and feasible in the neurologically ill patients with acute respiratory distress syndrome. Increased intracranial pressure and compromised cerebral perfusion pressure may occur with prone positioning. We propose a prone positioning protocol for the neurologically ill patients who require frequent neurologic examinations and intracranial monitoring. CONCLUSIONS: Although elevations in intracranial pressure and reductions in cerebral perfusion pressure do occur during proning, they may not occur to a degree that would warrant exclusion of prone ventilation as a treatment modality for patients with acute respiratory distress syndrome and concomitant neurologic diagnoses. In cases where intracranial pressure, cerebral perfusion pressure, and brain tissue oxygenation can be monitored, prone position ventilation should be considered a safe and viable therapy.